Problematika Pendidikan Era Society 5.0: Dampak Penggunaan Gadget pada Karakter Peserta Didik di MIS Islamiyah Ringinanom Ngawi - Susilowati, Ambar Dyan; Rossidy, Imron (ISLAMIKA, 2024)
The research objective of this article is to find out what factors support the intensity of gadget use among MIS Islamiyah Ringinanom students, what the impact of gadget use is on students, and solutions and recommendations that teachers and parents can make to deal with the impact of gadget use on students.In the era of society 5.0, humans live side by side with technologys, everyone uses technology. The development of technology also has an impact on the high use of technology such as gadgets. This research aims to examine the impact of high intensity of gadget use on the character of MIS Islamiyah Ringinanom students. This research uses a qualitative approach, data collection methods through interviews and observations, and documentation. The research results show that intense use of gadgets has a negative impact on students' character, namely a lack of sense of responsibility, underestimating religious aspects, decreased concentration in learning, and the emergence of anti-social and introverted attitudes. It is hoped that this research will be able to make a contribution to the field of education, especially in addressing the use of gadgets and paying more attention to the development of students' character.